Six Kenyan and Ugandan coffee companies and several institutions mainstream Regenerative Agriculture within their programs for 12,000 farmers - Rahn, Eric; Ocimati, Walter; Waswa, Boaz Shaban; Notenbaert, An (2025)
The Alliance of Bioversity International and CIAT and implementing partners and stakeholders developed a country-specific Regenerative Coffee Agriculture guidebooks for both Kenya and Uganda. The guidebooks are currently being used by six coffee partners working with over 12,000 farmers in both countries to support a transition to sustainable coffee production. Additionally, the guidebooks have influenced major investments, such as Starbucks’ regenerative coffee program in Ethiopia, and guided implementing the Periodic Table for Food Initiative, a project supported by the Rockefeller-Foundation.